Techniques for development of safety-related software for surgical robots. - Varley, P. (IEEE Transactions on information technology in biomedicine)
Regulatory bodies require evidence that software controlling potentially hazardous devices is developed to good manufacturing practices. Effective techniques used in other industries assume long time scales and high staffing levels and can be unsuitable for use without adaptation in developing electronic healthcare devices. This paper discusses a set of techniques used in practice to develop software for a particular innovative medical product, an endoscopic camera manipulator. These techniques include identification of potential hazards and tracing their mitigating factors through the project life-cycle.